Laberintos de tiempo y arena. Francisco Ayala, Korge Luis Borges y Julio Cortázar - López Calahorro, Inmaculada (Amaltea. Revista de Mitocrítica, 2009)
In this article we analise the relationship among different texts written by Francisco Ayala, Julio Cortázar and Jorge Luis Borges, under the perspective of the Laberynth, that is to say –El hechizado, “Casa tomada” and “La casa de Asterión”, respectively. We pretend to establish a relationship between their common elements and its time. We start from the friendship among the three authors in the 1940’s in Argentina, which influenced many other texts later on. We also pay attention to their work as translators in those years and their relationship to Kafka mainly. We analyse the structure of their laberynths and their shape into a house and the figure of the minotaur, under a double perspective, the contemplation and the spell. We finally establish an intertextual relationship between the literary works of Ayala and Borges.